Third-Generation Minimally Invasive Chevron Akin Osteotomy for Hallux Valgus. (January 2020) - Holme, Thomas J.; Sivaloganathan, Sivan S.; Patel, Beejal; Kunasingam, Kumar
Background: Multiple operative techniques have been developed for hallux valgus with varying success. The most recent developments in minimally invasive surgery have evolved into the third-generation minimally invasive chevron Akin (MICA) osteotomy. Good results have been shown from originator centers, but this is one of the first series from a nonoriginator center, and the first to use a validated patient-reported outcome measure. Methods: Forty consecutive patients undergoing third-generation MICA for hallux valgus were included. Primary outcome measures included Manchester-Oxford Foot Questionnaire (MOXFQ) and American Orthopaedic Foot & Ankle Society (AOFAS) scores and Coughlin satisfaction rates at 12 months. Secondary outcome measures included radiographic parameters, complications, and recurrence rates. Results: At 12 months, the MOXFQ score improved from 58 to 10 and the AOFAS score improved from 48 to 93, with 70% of patients reporting excellent outcomes and 30% good ones. Two cases started as mild, 29 cases as moderate, and 9 cases as severe as defined by radiographic criteria. Hallux valgus angles improved from 32 degrees to 12 degrees, and intermetatarsal angles improved from 13 degrees to 7 degrees. There were 4 cases of Akin screw removal for soft tissue irritation. There were no other complications, including recurrence. Conclusion: The third-generation MICA technique was a safe and effective approach to treating hallux valgus. Further research should focus on long-term outcomes and comparative data with other commonly performed operative techniques. Level of Evidence: Level IV, case series.